PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU TENTANG PIJAT BAYI DI RUMAH SAKIT UMUM DEWI SARTIKA KOTA KENDARI - Sukmawati (LPPM Universitas Ekasakti, 2024)
Babies really need the sensation of touch early in life to adapt to their environment. Gentle touching of the baby is a wonderful way of bonding between the baby and the parents. Parents play a very important role in providing good stimulation and stimulation to increase the development of children's potential to the maximum. The aim of this research is to determine the effect of Health Education on mothers' knowledge of Baby Massage at the Dewi Sartika General Hospital, Kendari City. This research uses the Quasi-Experimental Design method using one group pretest and posttest design. The population and sample in this study were mothers who had babies at the Dewi Sartika General Hospital with a total sample of 30 samples. The sampling technique is using Accidental Sampling. The research was conducted in March 2024. The research used the Wilcoxon test. the results of data processing using the Wilcoxon test obtained a p-value of 0.000 (? =< 0.05) which means Ha is accepted and H0 is rejected which means there is an influence of Health Education on mothers regarding Baby Massage at the Dewi Sartika General Hospital Kendari City where Ha is accepted and H0 is rejected.